A catalyst for dehydrogenation of ethylbenzene to styrene and a preparation method thereof
Patent Information
- Application Number
- CN202211714751.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-29
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2042-12-29
AI Technical Summary
[0023]本发明的乙苯脱氢制苯乙烯催化剂采用多孔氧化铁,与普通的氧化铁相比,本发明的改变了氧化铁原料的形貌,由于多孔氧化铁具备孔结构和比表面,从而使氧化钾与之反应生成多铁酸盐活性相时,也具备的一定的孔结构,使其具备更加暴露的活性中心,反应物分子更加容易到接触活性中心,同时在反应过程中有利于反应物和产物在活性位的吸脱附反应,以及在催化剂体系中的扩散这一动力学过程,因此,本发明的催化剂能表现出更高的催化活性和稳定性。此外,本发明的乙苯脱氢制苯乙烯催化剂的组分更简单,相较于更多种组分制成的催化剂,本发明的乙苯脱氢制苯乙烯催化剂在提高了催化活性和稳定性的同时,降低了催化剂的成本及制备催化剂的复杂程度。
Smart Images

Figure BDA0004026198950000041 
Figure BDA0004026198950000042 
Figure BDA0004026198950000061
Abstract
Description
Technical Field
[0001] This invention belongs to the field of catalyst preparation technology, specifically relating to a catalyst for the dehydrogenation of ethylbenzene to styrene and its preparation method. Background Technology
[0002] Currently, styrene is produced industrially through the dehydrogenation of ethylbenzene. One of the key technologies in this production method is the selection of a highly efficient dehydrogenation catalyst. Ethylbenzene dehydrogenation catalysts are primarily Fe-K-Ce-Mo based catalysts. The preparation methods for these catalysts often involve solid-phase mixing of catalyst components such as Fe, K, Ce, and Mo in the form of oxides or salts, kneading with water, extruding, drying, and calcining. Examples include patents CN03150720 and CN10023611.9. However, these iron-potassium series ethylbenzene dehydrogenation catalysts mainly use industrial dye iron oxide as the main active component. Sodium carboxymethyl cellulose is added to bind the iron oxide to the other components, forming a certain porous structure after calcination. This affects the diffusion of reactants and products within the catalyst system during the reaction, leading to catalyst coking and low stability.
[0003] CN200910057804.4 discloses a catalyst for the dehydrogenation of crude ethylbenzene to styrene and its preparation method. It mainly addresses the problems of suboptimal pore distribution, excessive micropores, easy coking, short service life, and high purity requirements for the raw material ethylbenzene in previous technologies. By employing a technique of adding 1-10% of at least two of graphite, polystyrene microspheres, carboxymethyl cellulose, methyl cellulose, and guar gum powder to a Fe-K-Ce-Mo(W)-Mg-Ca catalytic system, and calcining the catalyst at 800-950℃, the above problems are effectively solved. This catalyst can be used in the industrial production of styrene, and is particularly suitable for the industrial production of styrene from crude ethylbenzene. The pores of this catalyst are mainly obtained through the site-occupancy effect of pore-forming agents graphite, polystyrene microspheres, carboxymethyl cellulose, methyl cellulose, and guar gum powder. The pore structure of this catalyst is mainly formed by the stacking of polystyrene microspheres. The macroporous structure obtained after calcination significantly reduces the catalyst strength, especially at high temperatures, easily causing catalyst structural collapse, severe loss of specific surface area, and a significant decrease in activity.
[0004] CN201110247189.0 discloses a catalyst and its preparation method for the dehydrogenation of methylethylbenzene to methylstyrene. The catalyst comprises the following components: 50-70% Fe₂O₃; 15-30% K₂O; 1-10% MgO; 1-10% CaO; 1-10% Nd₂O₃; and 1-10% MoO₃; the average pore size of the catalyst is distributed between 50-90 nm. The catalyst is prepared by adding a pore-forming agent during the blending process, mixing, stirring, granulating, drying, and calcining. The pore-forming agent is a mixture of guar gum powder and carbon nanotubes, with a weight ratio of guar gum powder to carbon nanotubes of 1:1 to 5:1; the amount of pore-forming agent used is 2-20% of the weight of Fe₂O₃ in the catalyst before calcination. Due to the high cost of carbon nanotubes and the difficulty and low yield of laboratory preparation methods, the cost of carbon nanotube-doped catalysts is too high, which is detrimental to industrialization.
[0005] CN201310112743.3 discloses a method for preparing a catalyst for the dehydrogenation of ethylbenzene to styrene. The catalyst is a composite oxide of iron, potassium, magnesium, cerium, and molybdenum. The preparation method includes: 1) preparation of nano-Ce₂O₃; 2) catalyst preparation, wherein a self-made nano-cerium trioxide is used, and the cerium source is introduced into the ethylbenzene dehydrogenation catalyst in a suitable ratio of cerium nitrate and nano-cerium trioxide. The resulting catalyst has macropores and a low specific surface area, maintaining high catalytic activity under low water-to-oil ratio conditions. However, this catalyst is prone to coking during use, leading to decreased stability and affecting catalyst lifespan.
[0006] Since the catalysts of the above invention mainly use iron oxide red or iron oxide yellow as raw materials, the catalysts are prone to carbon buildup during the reaction process, which reduces the stability and activity of the catalysts. Summary of the Invention
[0007] In view of the defects of the above-mentioned technology, the purpose of this invention is to provide a catalyst for the dehydrogenation of ethylbenzene to styrene and its preparation method. The catalyst for the dehydrogenation of ethylbenzene to styrene of this invention has higher stability and catalytic activity.
[0008] To achieve the above objectives, the present invention provides a catalyst for the dehydrogenation of ethylbenzene to styrene, which comprises the following components based on 100 parts by mass of the catalyst:
[0009] a) 74–85 parts of porous iron oxide, calculated as Fe2O3;
[0010] b) 8 to 15 parts of K, calculated as K2O;
[0011] c) 2 to 9 parts of Ce, calculated as Ce2O3;
[0012] d) 1 to 3 parts of Mo, calculated as MoO3.
[0013] In the ethylbenzene dehydrogenation to styrene catalyst of the present invention, preferably, the content of porous iron oxide is 75-80 parts, and the specific surface area of the porous iron oxide is 3-15 g / m². 2 The pore size is 2-15nm.
[0014] The ethylbenzene dehydrogenation catalyst for styrene production of the present invention preferably contains 9 to 13 parts of K2O.
[0015] The catalyst for the dehydrogenation of ethylbenzene to styrene of the present invention preferably has a Ce2O3 content of 3 to 7 parts.
[0016] The catalyst for the dehydrogenation of ethylbenzene to styrene of the present invention preferably has a MoO3 content of 2.2 to 2.8 parts.
[0017] The catalyst for the dehydrogenation of ethylbenzene to styrene of the present invention, preferably, involves the following preparation process of the porous iron oxide: ferric chloride and sodium dodecyl sulfonate are dissolved in deionized water and stirred thoroughly. The mixture is kept at a constant temperature of 35-45°C for 1-3 hours, then heated to 65-85°C and stirred for another 5-10 hours. During this period, sodium hydroxide is slowly added dropwise using a dropping funnel to ensure that the pH of the system is 6.0-7.5 at the end of the reaction. The reaction product is aged at room temperature for 4-6 hours, then filtered, washed, dried at 90-110°C for 1-3 hours, and then calcined in a muffle furnace at 450-600°C for 3-7 hours to obtain the porous iron oxide.
[0018] The ethylbenzene dehydrogenation to styrene catalyst of the present invention is preferably prepared as follows: Fe, K, Ce and Mo precursors are weighed and mixed according to the formula, deionized water is added and kneaded, extruded into strips, and granulated into particles with a diameter of 2-5 mm and a length of 3-10 mm; aged at room temperature for 2-8 hours, dried at 80-120°C for 2-5 hours, and calcined at 500-900°C for 2-6 hours to obtain the ethylbenzene dehydrogenation to styrene catalyst.
[0019] In the ethylbenzene dehydrogenation to styrene catalyst of the present invention, preferably, the precursor of K is at least one selected from oxides, nitrates, and carbonates.
[0020] In the ethylbenzene dehydrogenation to styrene catalyst of the present invention, preferably, the precursor of Ce is at least one selected from oxides, nitrates, and carbonates.
[0021] In the ethylbenzene dehydrogenation to styrene catalyst of the present invention, preferably, the precursor of Mo is at least one of an oxide or an ammonium salt.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] The ethylbenzene dehydrogenation to styrene catalyst of this invention uses porous iron oxide. Compared with ordinary iron oxide, the morphology of the iron oxide raw material of this invention is modified. Due to the porous structure and specific surface area of the porous iron oxide, the active phase formed by the reaction of potassium oxide with it to generate polyferrate also possesses a certain porous structure, giving it more exposed active sites. Reactant molecules can more easily reach and contact the active sites. At the same time, it is beneficial to the adsorption and desorption reactions of reactants and products at active sites and the diffusion kinetics in the catalyst system during the reaction. Therefore, the catalyst of this invention exhibits higher catalytic activity and stability. In addition, the composition of the ethylbenzene dehydrogenation to styrene catalyst of this invention is simpler. Compared with catalysts made with more components, the ethylbenzene dehydrogenation to styrene catalyst of this invention improves catalytic activity and stability while reducing the cost and complexity of catalyst preparation. Detailed Implementation
[0024] The following provides a detailed description of the embodiments of the present invention: These embodiments are implemented based on the technical solution of the present invention, and provide detailed implementation methods and processes. However, the scope of protection of the present invention is not limited to the following embodiments. Experimental methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions.
[0025] Detection method:
[0026] The specific surface area and pore size of porous iron oxide were measured using an UltraSorbX800 surface area analyzer.
[0027] Analysis method:
[0028] Using ethylbenzene as a raw material, the reaction is carried out at a pressure of atmospheric pressure to -0.07 MPa, a reaction temperature of 560-640℃, a water / ethylbenzene mass ratio of 0.8-2.0, and an ethylbenzene liquid hourly space velocity of 0.5-1.0 h⁻¹. -1 Under certain conditions, the raw materials come into contact with the catalyst to undergo a dehydrogenation reaction to produce styrene. The catalyst activity evaluation in this invention is carried out in an isothermal fixed-bed reactor, which is a stainless steel tube with an inner diameter of 25 mm, loaded with 100 mL of catalyst. The reaction solution is then analyzed by gas chromatography to determine the contents of ethylbenzene and styrene. The formulas for calculating the ethylbenzene conversion rate and the styrene selectivity are as follows:
[0029]
[0030]
[0031] The catalyst evaluation conditions are as follows: atmospheric pressure, reaction temperature of 610℃, water / ethylbenzene mass ratio of 1.8, and ethylbenzene liquid hourly space velocity of 1.0 h⁻¹. -1 .
[0032] Unless otherwise specified, the experimental methods described in the following embodiments are conventional methods; unless otherwise specified, the reagents and compounds are commercially available.
[0033] Example 1
[0034] Preparation method of porous iron oxide: 745.6 g of ferric chloride and 95 g of sodium dodecyl sulfonate were dissolved in deionized water and stirred thoroughly. The mixture was kept at 40 °C for 1.5 h. The reaction system was then heated to 80 °C and stirred for another 8 h, during which sodium hydroxide was slowly added dropwise using a dropping funnel to adjust the pH of the system. The amount of sodium hydroxide added was controlled so that the pH of the system was 7.0 at the end of the reaction. The reaction product was then aged at room temperature for 5 h, filtered, washed, and dried at 100 °C for 2 h to obtain an intermediate product. The intermediate product was calcined in a muffle furnace at 550 °C for 5 h to obtain porous iron oxide. The specific surface area of the obtained porous iron oxide was measured to be 4.2 g / m². 2 The aperture is 3.5 nm.
[0035] The prepared porous iron oxide, 100g potassium carbonate, 80g cerium nitrate, and 14g ammonium molybdate were mixed evenly, and 40g deionized water was added. The wet material was kneaded into a dough-like consistency suitable for extrusion. The dough was extruded and granulated into particles with a diameter of 3mm and a length of 10mm. The particles were aged at room temperature for 5 hours, dried in an oven at 120℃ for 4 hours, and then calcined in a muffle furnace at 830℃ for 3 hours to obtain the catalyst product. 100mL of the catalyst was loaded into an evaluation reactor, and the catalyst activity was evaluated at a reaction temperature of 620℃ and a water / ethylbenzene mass ratio of 1.8. The test results for styrene yield, styrene selectivity, and ethylbenzene conversion are shown in Table 3.
[0036] Example 2
[0037] The preparation method of porous iron oxide: 720g of ferric chloride and 100g of sodium dodecyl sulfonate were dissolved in deionized water and stirred thoroughly. The mixture was kept at 45℃ for 1 hour. Then, the reaction system was heated to 70℃ and stirred for another 10 hours. During this time, sodium hydroxide was slowly added dropwise using a dropping funnel to adjust the pH of the system. The amount of sodium hydroxide added was controlled so that the pH of the system was 7.5 at the end of the reaction. The reaction product was then aged at room temperature for 6 hours, filtered, washed, and dried at 110℃ for 1 hour to obtain an intermediate product. The intermediate product was calcined in a muffle furnace at 600℃ for 4 hours to obtain porous iron oxide. The specific surface area of the obtained porous iron oxide was measured to be 4.5 g / m². 2 The aperture is 6.5 nm.
[0038] The prepared porous iron oxide, 145g potassium nitrate, 95g cerium nitrate, and 24g molybdenum oxide were mixed evenly, and 80g deionized water was added. The wet material was kneaded into a dough-like consistency suitable for extrusion. The dough was extruded and granulated into particles with a diameter of 2mm and a length of 3mm. The particles were aged at room temperature for 8 hours, dried in an oven at 100℃ for 5 hours, and then calcined in a muffle furnace at 900℃ for 4 hours to obtain the catalyst product. 100mL of the catalyst was loaded into an evaluation reactor, and the catalyst activity was evaluated at a reaction temperature of 620℃ and a water / ethylbenzene mass ratio of 1.8. The test results for styrene yield, styrene selectivity, and ethylbenzene conversion are shown in Table 3.
[0039] Example 3
[0040] The preparation method of porous iron oxide: 712g of ferric chloride and 105g of sodium dodecyl sulfonate were dissolved in deionized water and stirred thoroughly. The mixture was kept at 35℃ for 3 hours. Then, the reaction system was heated to 65℃ and stirred for another 5 hours. During this time, sodium hydroxide was slowly added dropwise using a dropping funnel to adjust the pH of the system. The amount of sodium hydroxide added was controlled so that the pH of the system was 6.0 at the end of the reaction. The reaction product was then aged at room temperature for 4 hours, filtered, washed, and dried at 90℃ for 1 hour to obtain an intermediate product. The intermediate product was calcined in a muffle furnace at 450℃ for 7 hours to obtain porous iron oxide. The specific surface area of the obtained porous iron oxide was measured to be 4.0 g / m². 2 The aperture is 5.8 nm.
[0041] The prepared porous iron oxide, 140g potassium oxide, 110g cerium nitrate, and 45g ammonium molybdate were mixed evenly, and 75g deionized water was added. The wet material was kneaded into a dough-like consistency suitable for extrusion. The dough was extruded and granulated into particles with a diameter of 5mm and a length of 7mm. The particles were aged at room temperature for 2 hours, dried in an oven at 80℃ for 2 hours, and then calcined in a muffle furnace at 500℃ for 6 hours to obtain the catalyst product. 100mL of the catalyst was loaded into an evaluation reactor, and the catalyst activity was evaluated at a reaction temperature of 620℃ and a water / ethylbenzene mass ratio of 1.8. The test results for styrene yield, styrene selectivity, and ethylbenzene conversion are shown in Table 3.
[0042] Example 4
[0043] Preparation method of porous iron oxide: 760g of ferric chloride and 110g of sodium dodecyl sulfonate were dissolved in deionized water and stirred thoroughly. The mixture was kept at 40℃ for 3 hours. Then, the reaction system was heated to 85℃ and stirred for another 8 hours. During this time, sodium hydroxide was slowly added dropwise using a dropping funnel to adjust the pH of the system. The amount of sodium hydroxide added was controlled so that the pH of the system was 6.5 at the end of the reaction. The reaction product was then aged at room temperature for 5 hours, filtered, washed, and dried at 100℃ for 2 hours to obtain an intermediate product. The intermediate product was calcined in a muffle furnace at 550℃ for 3 hours to obtain porous iron oxide. The specific surface area of the obtained porous iron oxide was measured to be 5.6 g / m². 2 The aperture is 6.3 nm.
[0044] The prepared porous iron oxide, 124g potassium carbonate, 115g cerium nitrate, and 30g ammonium molybdate were mixed evenly, and 82g deionized water was added. The wet material was kneaded into a dough-like consistency suitable for extrusion. The dough was extruded and granulated into particles with a diameter of 3mm and a length of 5mm. The particles were aged at room temperature for 6 hours, dried in an oven at 80℃ for 2 hours, and then calcined in a muffle furnace at 850℃ for 2 hours to obtain the catalyst product. 100mL of the catalyst was loaded into an evaluation reactor, and the catalyst activity was evaluated at a reaction temperature of 620℃ and a water / ethylbenzene mass ratio of 1.8. The test results for styrene yield, styrene selectivity, and ethylbenzene conversion are shown in Table 3.
[0045] The active component contents of the catalysts obtained in Examples 1-4 are shown in Table 1.
[0046] Table 1 Content of active components in catalysts in examples
[0047]
[0048] Comparative Examples 1-3
[0049] The catalyst preparation methods of Comparative Examples 1-3 are the same as those of Example 1, except that: in Comparative Example 1, porous iron oxide is replaced with iron oxide red; in Comparative Example 2, porous iron oxide is replaced with iron oxide yellow; and in Comparative Example 3, porous iron oxide is replaced with half the mass of iron oxide red and half the mass of iron oxide yellow. The component contents are shown in Table 2, and the performance of the prepared catalysts are shown in Table 3.
[0050] Table 2 Content of active components in comparative catalysts
[0051]
[0052] Table 3 Catalyst performance test results
[0053] Example 1 95.6 75.2. 70.1 Example 2 95.8 75.4 70.3 Example 3 95.1 74.8 69.3 Example 4 95.3 74.1 69.8 Comparative Example 1 94 69.6 64.2 Comparative Example 2 94.2 68.7 63.2 Comparative Example 3 94.3 70.2 65.1
[0054] The stability of the catalyst was investigated, and the evaluation results are shown in Table 4.
[0055] Table 4. Stability test results of the catalyst
[0056]
[0057] As can be seen from Tables 3 and 4, the catalyst prepared using the porous iron oxide of the present invention as raw material has higher catalytic activity and stability compared with iron oxide red, iron oxide yellow, or a mixture of iron oxide red and iron oxide yellow (comparative example).
[0058] In summary, the ethylbenzene dehydrogenation to styrene catalyst provided by this invention has the advantages of higher catalytic activity and stability.
[0059] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the present invention.
Claims
1. A catalyst for the dehydrogenation of ethylbenzene to styrene, characterized in that, Based on a catalyst mass content of 100 parts, it includes the following components: a) 74–85 parts of porous iron oxide, calculated as Fe2O3; b) 8 to 15 parts of K, calculated as K2O; c) 2 to 9 parts of Ce, calculated as Ce2O3; d) 1 to 3 parts of Mo, calculated as MoO3; The preparation process of the porous iron oxide is as follows: ferric chloride and sodium dodecyl sulfonate are dissolved in deionized water and stirred thoroughly. The mixture is kept at 35-45℃ for 1-3 hours, then heated to 65-85℃ and stirred for another 5-10 hours. During this period, sodium hydroxide is slowly added dropwise using a dropping funnel to ensure that the pH of the system is 6.0-7.5 at the end of the reaction. The reaction product is aged at room temperature for 4-6 hours, then filtered, washed, dried at 90-110℃ for 1-3 hours, and then calcined in a muffle furnace at 450-600℃ for 3-7 hours to obtain the porous iron oxide.
2. The catalyst for the dehydrogenation of ethylbenzene to styrene according to claim 1, characterized in that, The porous iron oxide content is 75-80 parts, and the specific surface area of the porous iron oxide is 3-15 g / m². 2 The pore size is 2-15nm.
3. The catalyst for the dehydrogenation of ethylbenzene to styrene according to claim 1, characterized in that, The K2O content is 9 to 13 parts.
4. The catalyst for the dehydrogenation of ethylbenzene to styrene according to claim 1, characterized in that, The Ce2O3 content is 3 to 7 parts.
5. The catalyst for the dehydrogenation of ethylbenzene to styrene according to claim 1, characterized in that, The content of MoO3 is 2.2 to 2.8 parts.
6. The catalyst for the dehydrogenation of ethylbenzene to styrene according to any one of claims 1 to 5, characterized in that, The preparation process of the ethylbenzene dehydrogenation to styrene catalyst is as follows: Weigh porous iron oxide and K, Ce and Mo precursors according to the formula and mix them. Add deionized water and knead. Extrude into strips and granulate into particles with a diameter of 2-5 mm and a length of 3-10 mm. Age at room temperature for 2-8 hours, dry at 80-120℃ for 2-5 hours, and calcine at 500-900℃ for 2-6 hours to obtain the ethylbenzene dehydrogenation to styrene catalyst.
7. The catalyst for the dehydrogenation of ethylbenzene to styrene according to claim 1, characterized in that, The precursor of K is at least one of oxides, nitrates, and carbonates.
8. The catalyst for the dehydrogenation of ethylbenzene to styrene according to claim 1, characterized in that, The precursor of Ce is at least one of oxides, nitrates, and carbonates.
9. The catalyst for the dehydrogenation of ethylbenzene to styrene according to claim 1, characterized in that, The precursor of Mo is at least one of oxides and ammonium salts.
Citation Information
Patent Citations
Catalyst for preparing styrene through dehydrogenation by using rough ethylbenzene and preparation method thereof
CN101992095A
Catalyst for preparing methyl styrene by methyl ethylbenzene dehydrogenation and preparation method
CN102950005A
A preparation method of a catalyst for dehydrogenation of ethylbenzene to styrene
CN104096568B
Oxide catalyst used in ethyl benzene dehydrogen for preparing phenyl ethylene
CN1589963A
Method for preparing dehydrogenation catalyst
CN101658790A